Adverse Maternal and Neonatal Outcomes in Indicated Compared with Spontaneous Preterm Birth in Healthy Nulliparas; a secondary analysis of a randomized trial - Tita, Alan T. (Am J Perinatol, 2017)
OBJECTIVE: To compare the risks of adverse maternal and neonatal outcomes associated with spontaneous (SPTB) vs. indicated (IPTB) preterm birth. METHODS: A secondary analysis of a multicenter trial of vitamin C and E supplementation in healthy low-risk nulliparous women. Outcomes were compared between women with SPTB (due to spontaneous membrane rupture or labor) and those with IPTB (due to medical or obstetric complications). A primary maternal composite outcome included: death, pulmonary edema, blood transfusion, adult respiratory distress syndrome, cerebrovascular accident, acute tubular necrosis, disseminated intravascular coagulopathy or liver rupture. A neonatal composite outcome included: neonatal death, RDS, grades 3 or 4 IVH, sepsis, NEC, or retinopathy of prematurity. RESULTS: Of 9867 women, 10.4% (N=1038) were PTBs; 32.7% (n=340) IPTBs and 67.3% (n=698) SPTBs. Compared with SPTB, the composite maternal outcome was more frequent in IPTB – 4.4% vs. 0.9% (adjusted OR 4.0 95% CI 1.4–11.8) as were blood transfusion and prolonged hospital stay (3.2 and 3.7 times respectively). The frequency of composite neonatal outcome was higher in IPTBs (aOR 1.8; 1.1–3.0), as were RDS (1.7 times), SGA<5(th) percentile (7.9 times) and NICU admission (1.8 times). CONCLUSION: Adverse maternal and neonatal outcomes were significantly more likely with IPTB than with SPTB.